SPE Middle East Oil and Gas Show and Conference 2005
DOI: 10.2118/93621-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production Optimization in ESP Completions with Intelligent Well Technology by Using Downhole Chokes to Optimize ESP Performance

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractAccelerated production, increased ultimate recovery, and reduced interventions are goals of any operating company. It is now possible to attain all of these goals simultaneously by retrofitting intelligent well technology to an existing, conventional completion. This task is much more complex when the new technology must be installed in conjunction with artificial lift, such as an electric submersible pump (ESP). However, new technology and procedures have ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…A recent study (Vachon and Furui 2005) has shown that pumpassisted production could be achieved from both zones by use of a downhole SESP and a downhole choke. An alternative is a DESP completion and commingled production.…”
Section: Multiple Production Zonesmentioning
confidence: 99%
“…A recent study (Vachon and Furui 2005) has shown that pumpassisted production could be achieved from both zones by use of a downhole SESP and a downhole choke. An alternative is a DESP completion and commingled production.…”
Section: Multiple Production Zonesmentioning
confidence: 99%
“…(Olijnik et al, 1996, Anderson, 2005, Vachon and Furui, 2005, Ali and Shafiq, 2008, Ansah et al, 2009, Soegiyono et al, 2010, Al-Mohanna et al, 2011. Related procedures and equipment are available for gas lifted wells with I-completions (Cedeno and Ortiz, 2007, Vasper, 2008, Iyamu et al, 2008, Stephenson et al, 2010.…”
mentioning
confidence: 99%
“…They describe how the ICV may be used to shut-in zones to avoid cross-flow when the AL is halted. (Vachon and Furui, 2005) optimized an ESP installed in I-well completions with ICVs. The ICV can be operated to reduce the drawdown by applying an extra pressure drop across the sand face.…”
mentioning
confidence: 99%
See 1 more Smart Citation